Study of Demodex mites: Challenges and Solutions. (23rd December 2015) - Lacey, N.; Russell‐Hallinan, A.; Powell, F.C.
Abstract: Demodex mites are the largest and most complex organisms of the skin microflora. How they interact with the innate and adaptive immune systems is unknown. Their potential to have a pathogenic role in the causation of human skin disorders causes continued speculation. With growing interest in the microflora of human skin and its relevance to cutaneous health, the role of Demodex mites needs to be better understood. The main challenges facing scientists investigating the role of these organisms and possible solutions are reviewed under the following headings: (1) Determining the mite population in skin, (2) Transporting, extracting and imaging live mites, (3) Maintaining mites viable ex vivo and (4) Establishing methods to determine the immune response to Demodex mites and their internal contents.